Heavy Alcohol Use, Marijuana Use, and Concomitant Use by Adolescents Are Associated with Unique and Shared Cognitive Decrements. (22nd September 2014) - Winward, Jennifer L.; Hanson, Karen L.; Tapert, Susan F.; Brown, Sandra A.
Abstract To assess recovery of cognitive effects, we investigated neuropsychological performance after 1 month of monitored abstinence in teens with histories of heavy episodic drinking, protracted marijuana use, or concomitant use of alcohol and marijuana. Adolescents (ages 16–18 years) with histories of heavy episodic drinking (HED; n=24), marijuana use (MJ; n=20), both heavy alcohol and marijuana use (HED+MJ; n=29), and socio-demographically similar control teens (CON; n=55) completed a neuropsychological battery following 4 weeks of monitored abstinence. Groups were similar on 5th grade standardized test scores, suggesting comparable academic functioning before onset of substance use. Relative to CON, HED showed poorer cognitive flexibility (p=.006), verbal recall (p=.024), semantic clustering (p=.011), and reading skills (p=.018). MJ performed worse than CON on inhibition task accuracy (p=.015), cued verbal memory (p=.031), and psychomotor speed (p=.027). Similar to HED youth, HED+MJ showed differences relative to CON on cognitive flexibility (p=.024) and verbal recall (p=.049). As with MJ teens, HED+MJ showed poorer task accuracy (p=.020). Unique to the HED+MJ group was poorer working memory (p=.012) relative to CON. For all substance using participants, worse performance across domains correlated with more lifetime use of alcohol and of marijuana, more withdrawal symptoms from alcohol, and earlier age of onset of marijuana use (ps<.05). Heavy alcohol use, marijuana use, and concomitant use of both substances during adolescence appear to be associated with decrements in cognitive functioning, and each substance (or combination of substances) may be linked to poorer performance in specific cognitive domains (JINS, 2014, 20, 784–795).